Analisis Pengaruh Gula Aren dan Gula Pasir terhadap Berat dan Cooking Loss pada Hard Cookies - Vania Elsya Defanbi; Keisha Marjorie Rosidi; Syifa Amalia Shoddiq; Fakhri Safwan; Nathanael Bima Wisaputera; Efrina .; Leila Siti Chairani (GLOBAL SCIENTS PUBLISHER, 2026)
Hard cookies are baked bakery products with a crunchy texture that are widely consumed across all age groups. The type of sugar used in hard cookies production is known to influence not only sensory attributes but also the physical characteristics of the final product, particularly weight and cooking loss. This study aims to analyze the effect of palm sugar and granulated sugar on the weight and cooking loss (spread/diameter change) of hard cookies. This research employed a qualitative approach through a literature study (library research), supported by direct observation of the baking process using an identical dough formulation for both sugar types, baked at 150°C for 20 minutes. The results showed that both palm sugar and granulated sugar treatments produced the same total dough weight of 260 grams, yielding approximately 20 pieces of hard cookies with an average weight of 13 grams each. The dough diameter increased from 4.5 cm before baking to 5 cm after baking for both treatments, an increase of 0.5 cm. These findings indicate that, under the formulation and baking conditions applied in this study, the use of palm sugar and granulated sugar did not produce a significant difference in the weight and spread characteristics of hard cookies, although the two sugars are theoretically known to differ in melting behavior and water-binding capacity.